2017
DOI: 10.1248/bpb.b16-00848
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Elevation Associated with Topical Prostaglandin F2α Analogs: An Analysis of the Different Spontaneous Adverse Event Report Databases

Abstract: Topical prostaglandin F2α (PGF2α) analogs are widely used as the first line of therapy for glaucoma. Systemic PGF2α is suggested to increase blood pressure. Some ophthalmic formulations with β-receptor blocking or α-receptor stimulating actions are reported to cause systemic adverse events such as a decrease in heart rate and blood pressure. The objective of this study was to evaluate the association between topical Key words prostaglandin F2α analog; blood pressure elevation; spontaneous reporting database; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
5
1
Order By: Relevance
“…An effect on cardiac function of exposure to the FP antagonists OBE002 or its parent OBE022 could be excluded despite the reported action of FP agonists on cardiac function in vitro 8,9,11,[30][31][32] and reports of blood pressure elevation in response to topical application of FP agonists. 33 This is consistent with previous clinical studies of allosteric FP antagonists that showed no QTc prolongation attributable to drug administration. 12 The predicted C max values from the concentration-response analysis model were in close agreement with the empirical data gathered in this study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…An effect on cardiac function of exposure to the FP antagonists OBE002 or its parent OBE022 could be excluded despite the reported action of FP agonists on cardiac function in vitro 8,9,11,[30][31][32] and reports of blood pressure elevation in response to topical application of FP agonists. 33 This is consistent with previous clinical studies of allosteric FP antagonists that showed no QTc prolongation attributable to drug administration. 12 The predicted C max values from the concentration-response analysis model were in close agreement with the empirical data gathered in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Some of the concentration–QTcF models for parent OBE002 (models both and OBE022; Table ) tended to indicate a nonsignificant negative slope. An effect on cardiac function of exposure to the FP antagonists OBE002 or its parent OBE022 could be excluded despite the reported action of FP agonists on cardiac function in vitro and reports of blood pressure elevation in response to topical application of FP agonists . This is consistent with previous clinical studies of allosteric FP antagonists that showed no QTc prolongation attributable to drug administration .…”
Section: Discussionsupporting
confidence: 86%
“…The prodrug was safe and well tolerated across all dosing regimens. Significant changes in vital signs were not observed in this trial, despite the previously reported blood pressure elevation in response to topical application of FP agonists [41] and the association of tocolytic medication with hypotensive effects [42,43]. After oral administration, the prodrug was readily transformed into its metabolite OBE002.…”
Section: Discussioncontrasting
confidence: 53%
“…However, some reports showed the systemic adverse events by ophthalmic formulations. 11 13) As for PGF2a formulations, a study using a diŠerent nationwide database exhibited the association between topical PGF2a analogs and blood pressure elevation, 14) which is another pharmacological action of the PGF2a. Accordingly, it is possible for topical PGF2a analogs to cause systemic adverse events such as asthma.…”
Section: Discussionmentioning
confidence: 99%